Trimming and pH Effects on Nickel Ion Release from Stainless Steel Crowns of Primary Teeth - Arab-Nozari, Milad; Shokrzadeh, Mohammad; Zamehran, Nastaran; Yazdani Charati, Jamshid; Nahvi, Azam (UI Scholars Hub, 2020)
Objective: Stainless steel crowns (SSCs) are preformed metal crowns used to restore severely decayed primary teeth. The aim of this study is to evaluate the effects of pH changes and SSC margin trimming on nickel release in artificial saliva solution. Methods: A total of 90 SSCs were divided into three groups and placed in 35 ml of artificial saliva of pH 6.8, 5, and 3.5. Another group consisting 30 SSCs with trimmed margins was placed in saliva of pH 6.8. All SSCs were incubated at 37°C. The concentration of released nickel was assessed on days 1, 7, 14, 21, and 28 by atomic absorption spectrophotometry. Results: The highest concentrations of nickel were released on the first day in all groups. Nickel release increased with decreasing pH, and the differences observed were statistically significant on days 1, 7, 14, and 28. SSC trimming caused a significant increase in nickel release on all days except day 21. Conclusion: The concentration of nickel increased in saliva of low pH. The highest levels of nickel were released with SSC margin trimming because of the loss of integrity of the margins.